PENINGKATAN PRESTASI BELAJAR SISWA MELALUI SELF-REGULATED LEARNING - Muhammad Nur Wangid (Jurnal Cakrawala Pendidikan, 2004)
An educational system should be able to develop students' ability to learn. Students who have good learning habits and ability could begiven the J:eSPonsibilit¥ and ability ofregulating their own learning activities. Itmeans that it would be the students themselves who would execute the processes of exploration, inquiry, and learning and also conceptualize their activities. Students' learning activities would not work ifthe teacher's conceptofinstruction still uses the approach ofthe "content delivery system", which means that the teacher continually gives with the students merely taking and accepting. This kind ofinstructional approach principally would produce passive and dependent students, who always wait to be spoon-fed bythe teacher. Such an attitude passivity anddependence in students would affect them by decreasing their enthusiasm for active learning, which, in tum, would yield a low academic perfonnance, preventing them from getting a passing grade, make them fail, and possibly even cause them to drop out. On the face ofsuch a problem, there has come the concept ofself-regulated learning, a concept that tries to explain how students canberegula tors oftheirownlearning activities.Self-regulated learning is the kind oflearning that occurs because of the influence of students' self-generated thoughts, feelings, strategies, and behaviors which are oriented toward the attainment oflearning goals. Here it is important that students' initiative starts their learning activity. Active, dynarnic, and creative students usually have much initiative to doing some activities. Once they know the direction to the objectives, they would generate thoughts, feelings, strategies, and behaviors oriented toward the attainment ofgoals. So the basic components of self-regulated learning are self-regula tion ofcognition, self-regulation ofmotivation and emotion, and self-regulation ofbehavior. Teachers can help students become more self-regulated. Some ways to teach self-regulated learning are explicit instruction, direct reflection, and meta-cognitive discussion. Two modeh{that could be followed are those called Cycle ofSelf-Regulated Learning, and ACyclical Model ofSelf regulated Learning from Zimmerman. Both models, however, are alike principally. They start with planning, implementation, and e valuation ofthe chosen strategies. Results ofthe researches have proven that self-regulated learning correlates significantly with academic performance in primary, middle, and high school students. Keywords: promoting academic performance, self-regulated learning.